Effects of long-term fluoride exposure are associated with oxidative biochemistry impairment and global proteomic modulation, but not genotoxicity, in parotid glands of mice - Miranda, Giza Hellen Nonato; De Oliveira Lima, Leidiane Alencar; Bittencourt, Leonardo Oliveira; Dos Santos, Savio Monteiro; De Souza, Michel Platini Caldas; Nogueira, Lygia Sega; De Oliveira, Edivaldo Herculano Corrêa; Monteiro, Marta Chagas; Dionizio, Aline; Leite, Aline Lima; Pessan, Juliano Pelim [UNESP]; Buzalaf, Marilia Afonso Rabelo; et al. (Public Library of Science (PLoS), 2022)
Background Fluoride has become widely used in dentistry because of its effectiveness in caries control. However, evidence indicates that excessive intake interferes with the metabolic processes of different tissues. Thus, this study aimed to investigate the effects of long-term exposure to F on the parotid salivary gland of mice, from the analysis of oxidative, proteomic and genotoxic parameters. Materials and methods The animals received deionized water containing 0, 10 or 50 mg/L of F, as sodium fluoride, for 60 days. After, parotid glands were collected for analysis of oxidative biochemistry, global proteomic profile, genotoxicity assessment and histopathological analyses. Results The results revealed that exposure to fluoride interfered in the biochemical homeostasis of the parotid gland, with increased levels of thiobarbituric acid reactive species and reduced glutathione in the exposed groups; as well as promoted alteration of the glandular proteomic profile in these groups, especially in structural proteins and proteins related to oxidative stress. However, genotoxic assessment demonstrated that exposure to fluoride did not interfere with DNA integrity in these concentrations and durations of exposure. Also, it was not observed histopathological alterations in parotid gland. Conclusions Thus, our results suggest that long-term exposure to fluoride promoted modulation of the proteomic and biochemical profile in the parotid glands, without inducing damage to the genetic component. These findings reinforce the importance of rationalizing the use of fluorides to maximize their preventative effects while minimizing the environmental risks.